Художнє втілення рис ‘нової щирості’ в романі Софії Андрухович Амадока - Гребенюк, Тетяна Володимирівна; Hrebeniuk, T. (My University, 2021)
W artykule poddano analizie powieść Sofii Andruchowycz Amadoka jako arty styczną eksplikację istotnego we współczesnych badaniach socjohumanitarnych pojęcia postpamięci, zaproponowanego przez Marianne Hirsch, czyli „struktury inter- i transpokoleniowego przekazu trau matycznej wiedzy i doświadczenia”. Sofia Andruchowycz proponuje czytelnikowi rodzaj ekspery mentu – zaszczepienia sztucznych wspomnień, transmitowania traumatycznych przeżyć poprzednich pokoleń człowiekowi, który stracił pamięć z powodu rany odniesionej na wojnie w Donbasie. Celem pracy jest analiza zmysłowości powieści Amadoka w kontekście kojarzonego ze światopoglądem me tamodernu etycznego i estetycznego ruchu ‘nowej szczerości’. W szczególności przedmiotem uwagi jest realizacja w powieści ukraińskiej pisarki takich cech artystycznego ruchu ‘nowej szczerości’, jak poważny, nieironiczny ton narracji; odwoływanie się do emocji, uczuć na kartkach książki (lub zauważanie ich nieobecności tam, gdzie powinny być); świadomość sprzeczności i ambiwalencji ludzkich uczuć; wątpliwości podmiotu co do jego własnej zdolności do bycia szczerym; manipulacja wiarą i zaufaniem czytelnika; waga tego, co zostało „poza stroną”. . The article deals with the novel Amadoka by Sofia Andrukhovych as a explication in fiction of Marianne Hirsch’s notion of ‘postmemory’. This notion, which is of great significant in contemporary social studies and humanities, means a “structure of the inter- and trans-generational transmission of traumatic knowledge and experience”. What Sofia Andrukhovych offers the reader is something of an experiment – implanting artificial memories, transferring the previous generations’ traumatic experience to a person who has lost their memory by being wounded in the Donbas war. The aim of the research is to analyse the sensual nature of the novel Amadoka in terms of ‘New Sincerity’, an aesthetically and ethically relevant trend associated with the metamodern worldview. The primary focus is on how features of the ‘new sincerity’ are expressed in Andrukhovych’s novel. These features include: seriousness and a lack of irony in narrative; reference to emotions and feelings in the novel (or a fixation with their absence in the moments where they should have been present); awareness of the contradictory nature and ambivalence of human feelings; the individual’s doubts in his or her ability to be sincere; manipulations with the reader’s faith and trust; and the importance of that was left “off the page”.
Artystyczne ucieleśnienie cech ‘nowej szczerości’ w powieści Sofii Andruchowycz Amadoka
The artistic embodiment of the features of ‘new sincerity’ in Sofia Andrukhovych’s novel Amadoka
Гребенюк Т. В. - ORCID: 0000-0003-1910-5411.
Keywords: теорія літератури; powieść Amadoka; postpamięć; nowa szczerość; metamodernizm; narracja; the novel Amadoka; postmemory; ‘new sincerity’; metamodernism; narrative